There's a very easy way to convert from a logarithm in any base to a logarithm in any other base. The "base conversion formula" works like this: to convert from base a to base b,
log_b (x) = log_a (x) / log_a (b)
(Imagine that the _b and _a are little subscript b's and a's.)
In your case, you want to convert from base a to base 10, so we'll use the typical notation of "log" without a base to indicate base 10.
log x = log_a (x) / log_a (10)
In other words, to convert a log in any base to base 10, just divide by the log (base a) of 10.
Hope that helps!
2006-10-16 02:24:51
·
answer #1
·
answered by Jay H 5
·
0⤊
1⤋
log x to the base a
= log x to the base 10/log a to the base 10
2006-10-16 02:27:35
·
answer #2
·
answered by raj 7
·
0⤊
1⤋
Logb(x) = Loga(x)/Loga(b)
Here is why it works
If Loga(x) = A then x = a^A
and if Logb(x) = B then x = b^B
Now take logs to the base a of both sides to get
Loga(x) = B *Loga(b)
and so Loga(x) = Logb(x) * Loga(b)
rearrange to get Logb(x) = Loga(x) / Loga(b)
2006-10-16 03:21:37
·
answer #3
·
answered by Stewart H 4
·
0⤊
1⤋
just follow simple fromula :
log to base e = 2.303 X log to base 10
2006-10-16 18:39:17
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
There is no log e base a.
2006-10-16 02:25:13
·
answer #5
·
answered by ars32 3
·
0⤊
2⤋
We have to calculate log(a)x = log(10)(?)
Let a^y=x, such that y=log(a)x
Now, log(a)x = [log(10)x]/[log(10)a]
Therefore, log(a)x = [log(10)x] * log(10)a
2006-10-16 05:03:14
·
answer #6
·
answered by Rohan 1
·
0⤊
1⤋